An Assessment of Konza Prairie Community Health Center's Use of Prescription Assistance Programs - Williams, Emily (My University, 2015)
In 2013, the United States spent an average of $1000 per capita on prescription medication, over 40% more than any other country.1 High prescription medication costs have led people to skip filling prescription medications in order to save money. In 2013, one in five US adults did not fill a prescription due to expense.1 These costs have been challenging for many Americans, but have been particularly taxing for adults under 65 without prescription drug coverage.2 Many people without coverage are forced to decide between purchasing medication or paying the bills. High medication costs have resulted in 45% of people, without prescription coverage, skipping filling a prescription within the past year.2 To save money some patients are also not taking the prescriptions as directed. Thirty one percent of patients skipped a scheduled dose and 19% cut pills in half without the approval of a doctor or pharmacist.